Heard over the Iowa Birdline, March 1-May 31, 1992 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1992)
Summary of the Iowa Birdline update for March 1-May 31, 1992. Highlights of the update include first state record sightings of a Black Vulture and an American Swallow-tailed Kite. Other interesting observations of note include an April sighting of Eurasian Wigeons and May sightings of Snowy Plover, Black-necked Stilt, Whimbrel, and Red Knot. Epson - sheet feed